Estimating the Demand for Informal Public Transport Evidence from Antananarivo, Madagascar - Iimi, Atsushi (The World Bank, 2022)
Informal public transport has been growing rapidly in many developing countries. Because urban infrastructure development tends to lag rapid population growth, informal public transport often meets the growing gap between demand and supply in urban mobility. Despite the rich literature primarily focused on formal transport modes, the informal transport sector is relatively unknown. This paper analyzes the demand behavior in the "informal" minibus sector in Antananarivo, Madagascar, taking advantage of a recent user survey of thousands of people. It finds that the demand for informal public transport is generally inelastic. Essentially, people have no other choice. While the time elasticity is estimated at -0.02 to -0.05, the price elasticity is -0.05 to -0.06 for short-distance travelers, who may have alternative choices, such as motorcycle taxi or walking. Unlike formal public transportation, the demand also increases with income. Regardless of income level, everyone uses minibuses. The estimated demand functions indicate that people prefer safety and more flexibility in transit. The paper shows that combining these improvements and fare adjustments, the informal transport sector can contribute to increasing people's mobility and reducing traffic congestion in the city
Keywords: Demand Analysis; Energy; Energy Production and Transportation; Environment; Informal Public Transport; Informal Transportation; Infrastructure Economics and Finance; Pollution Management and Control; Population Growth; Private Participation in Infrastructure; Traffic Congestion; Transport Globl Knowledge and Expertise; Urban Environment; Urban Infrastructure; Urban Mobility; Urban Transport; Urban Transportation